KEWIRAUSAHAAN LINGKUNGAN DI SEKTOR PUBLIK: STUDI KASUS BANK SAMPAH RAYASA DIDESA KAUMAN KECAMATAN BOJONEGORO - Heny Suhindarno; Mochtar Setijohadi; Lita Tri Cahyaningrum (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study aims to analyze environmental entrepreneurship practices in the public sector through a case study of the Rayasa Waste Bank in Kauman Village, Bojonegoro Regency, Indonesia. The research employs a descriptive qualitative approach to explore how environmental entrepreneurship is implemented through community-based waste management and circular economy practices. The study is grounded in the Circular Economy Theory proposed by the Ellen MacArthur Foundation (2013), which emphasizes three core principles: designing out waste and pollution, keeping products and materials in use, and regenerating natural systems. The findings indicate that Rayasa Waste Bank has successfully applied these principles through several innovative programs. The principle of designing out waste and pollution is reflected in the production of Mijel soap from used cooking oil, which reduces household waste while creating economic value. The principle of keeping products and materials in use is implemented through a waste savings system that encourages residents to treat waste as a valuable resource. Meanwhile, the principle of regenerating natural systems is realized through the production of eco-enzymes from organic waste, contributing to environmental restoration and ecological awareness. The collaboration among local government, waste bank managers, and community members demonstrates the important role of the public sector in facilitating green entrepreneurship. Despite challenges related to infrastructure, human resources, and market access, Rayasa contributes to SDG 12 (Responsible Consumption and Production) and serves as a sustainable model of community-based environmental entrepreneurship